2003
DOI: 10.1097/01.jom.0000083032.56116.88
|View full text |Cite
|
Sign up to set email alerts
|

Hand Lacerations and Job Design Characteristics in Line-Paced Assembly

Abstract: This study investigated risk factors for laceration injuries among workers employed in line-paced manufacturing assembly operations. Most lacerations (76% of 576) occurred on the hands and fingers (grouped as "hand" lacerations). On average, 37% of surveyed workers reported at least one laceration to the hand in the preceding year, resulting in an overall hand laceration rate of 83 per 100 workers per year. An inverse relationship was found between level of job routinization and hand lacerations, with progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, where tasks become more variable, that is when rotating jobs or doing repair work, the risk of a hand laceration may increase and require more, not less, PPE use. 26 This may be especially relevant in service, professional, and managerial occupations where persons may leave their job role to do some unusual hazardous task. The impact of safety training on doing an unusual task was highly discordant.…”
Section: Discussionmentioning
confidence: 99%
“…However, where tasks become more variable, that is when rotating jobs or doing repair work, the risk of a hand laceration may increase and require more, not less, PPE use. 26 This may be especially relevant in service, professional, and managerial occupations where persons may leave their job role to do some unusual hazardous task. The impact of safety training on doing an unusual task was highly discordant.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include machine-paced work in forestry and assembly operations (Bell & MacDonald, 2003;Lilley et al, 2002); piece rate work in forestry, manufacturing, and garment workers (Brisson, Vinet, Vezina, & Gingras, 1989;Kaminski, 2001;Sundstrom-Frisk, 1984); overtime in many industries, including forestry (Caruso, Hitchcock, Dick, Russo, & Schmit, 2004;Dembe, Erickson, Delbos, & Banks, 2005;Folkard & Lombardi, 2006;Lilley et al, 2002); and indicators of psychosocial strain, such as low decision latitude or poor relationships at work, in a wide range of industries (Bongers, de Winter, Kompier, & Hildebrandt, 1993;Bongers, Kremer, & ter Laak, 2002;d'Errico et al, 2007;Swaen, van Amelsvoort, Bultmann, Slangen, & Kant, 2004). Increased risk in manufacturing has been reported with greater labor intensity (i.e., faster work pace and fewer rest breaks; Grunberg, 1983).…”
Section: Consistency Of Study Findings With Other Literaturementioning
confidence: 99%
“…Bell et al reported an inverse relationship between the level of job routinization and hand lacerations, and most lacerations occurred among workers assigned to less routine (more variable) work patterns 20) . The level of job routinization is lower in the metal-machinery sector when compared to textile and mining sectors and the worker intervenes in the raw material, tools, system and the products with a resultant high level of hand-tool interaction.…”
Section: Industry Types In Wrhimentioning
confidence: 99%